Predictive role of frailty and malnutrition in rehospitalisation of cardiac failure patients: A literature review - Farhan Muhammad Qureshi; Ayyaz Ali Khan (Journal of the Pakistan Medical Association)
Frailty and malnutrition are two conditions that are frequently present in cardiac failure patients that eventually contribute to hospitalisation and recurrent admissions. Malnutrition and frailty are interrelated and a predictive indicator of hospitalisations and subsequent readmissions that worsen the prognosis of cardiac failure patients. Research does not typically measure both nutritional status and frailty together in cardiac failure patients, and they are not even considered when planning and implementing the interventions. The life quality can be improved by early identification of frailty secondary to malnutrition and timely nutritional interventions. Rehospitalisations after discharge due to these conditions significantly increase the risk of death which can be avoided. The current narrative review was planned to highlight frailty and malnutrition as predictive indicators of hospitalisations and subsequent readmissions. Attempts to reduce the social and economic burden owing to these conditions in cardiac failure patients have emerged as a major public health priority worldwide, particularly in the developing countries.